Pengaruh Struktur Kepemilikan Dan Struktur Modal Terhadap Nilai Perusahaan - Khoirunnisa Azzahra; Siti Chaerunisa Prastiani (Jurnal Ilmiah Raflesia Akuntansi, 2025)
Company value is a very important part for a company, this is because an increase in stock prices will reflect the prosperity of investors or shareholders, a high company value indicates that the company's performance is good and reflects the company's internal success in managing existing company resources. This study aims to provide empirical evidence on the effect of managerial ownership structure, Institutional Ownership Structure, sales growth and capital structure on Company Value in Properties and Real Estate sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The number of research samples was 19 Properties and Real Estate sector companies with the Purposive Sampling method. The method used is multiple linear regression descriptive statistical test, panel data regression model analysis, the selected model selection test is the Random Effect Model (REM), classical assumption test, multiple linear test and hypothesis test with the help of e-views version 12 statistical data processing. The results of this study indicate that simultaneously Managerial Ownership Structure, Institutional Ownership Structure and Capital Structure have an effect on Company Value. And partially Managerial Ownership Structure affects the company value while Institutional Ownership Structure and Capital Structure do not affect the Company Value. A good Managerial Ownership Structure is a positive signal that increases investor confidence and can encourage an increase in Company Value.